Pragmatism in IR: The Prospects for Substantive Theorizing. Issue 4 (13th May 2021) - Pratt, Simon Frankel; Schmidt, Sebastian; Avant, Deborah; Cochran, Molly; Jackson, Patrick Thaddeus; Farrell, Henry; Knight, Jack; Hellmann, Gunther
Abstract: The contributors to this forum all draw significantly from pragmatist philosophy and social theory for making sense of international politics. Collectively, we affirm the value of pragmatist work beyond metatheory and methodology, both politically and epistemically—that is, as both a moral project and an explanatory one. Indeed, we are especially united on the notion that pragmatism "bridges" the divide between these things, and several contributors focus their discussion on how. However, we differ in what exactly it means to offer a distinctly pragmatist explanation or a "substantive" pragmatist theory, as well as in how pragmatism allows us to navigate the analytical and ethical challenges of the field. Over ten years ago, an earlier forum in this journal helped establish that pragmatism had something to offer; with over a decade of scholarship and reflection since, we revisit and expand on the question of how to deliver on it.